Use of toxicants baiting for reduction of wild boar populations in African swine fever disease management – implications for biodiversity and legislation - G. Balieva; D. Tanchev (Bulgarian Journal of Veterinary Medicine, 2024)
Wild animals appear to be a key factor in the occurrence, transmission and prevalence of a myriad of contagious animal diseases, being natural reservoirs, vectors or both. This role is played by wild boars in the African swine fever (ASF) transmission to domestic pigs. ASF entered the European Union in 2014 and since then lots of measures have been implemented to bring the disease under control. Bulgaria also tried to introduce new measures for reduction of wild boar populations, regarding ASF through legislative amendments. Proposals in the Bulgarian Law on hunting and game protection from 2020 tried to make legitimate wild boar culling with some unselective approaches like the use of baits with chemical poisonous or intoxicating substances. This provoked the authors to study the experience of other countries on particular toxicants used for baiting for control of wild boar populations. We investigated the available scientific literature on the selective character of chemical baiting and the effect on non-target species. Moreover, the participation of different stakeholders in the process of development and implementation of the mentioned measures was discussed. Thus, proposals were made for better preparatory, scientific and efficiency investigation at the preliminary stage of animal disease control measures development.